When Higher Education Meets Sustainable Development of Rural Areas: Lessons Learned from a Community–University Partnership - Maria Cecilia Mancini; Filippo Arfini; Marianna Guareschi (Social Sciences, 2022)
Sustainable development in mountain areas faces numerous socioenvironmental and economic challenges that public institutions have sought to address for decades. The EU is increasingly demanding Higher Education Institutions be more socially relevant and responsible in addressing the needs of these often-underserved communities. To this end, one central principle of the Erasmus+ Project 2014–2020, also consolidated by the Programme 2021–2027, has been to enhance the development, transfer, and implementation of innovative practices fostering social engagement at the local and international levels. The paper describes a case study developed in the “Socially Engaged Universities—(SEU)” project, co-funded by the Erasmus+ Programme 2014–2020, which aimed to strengthen the cooperation between universities and local communities. A local foundation and the University of Parma co-piloted a project to strengthen the short supply chains of a group of farmers in the Italian Appennines. The partnership identified factors that fostered and hampered the effectiveness of community–university partnerships. We propose some final recommendations to ensure that sustainable rural development fully leverages university resources. This includes higher education teaching and research programmes tailored toward the needs of the local community.